Estado nutricional de crianças de municípios de linha de fronteira internacional brasileira e de centros municipais de educação infantil de Foz do Iguaçu-PR - Santos, Clenise Maria Reis Capellani dos (2021)
Although childhood is a critical period of life, there is a scarcity of ecological studies on the nutritional status of children aged 0 to 5 years and socioeconomic factors and the built environment in Brazilian border municipalities. The objective was to analyze spatially and temporally the nutritional profile of children aged 0 to 5 years old from Brazilian international border line 119 municipalities and spatially the nutritional profile of 6067bchildren attending CMEIS in Foz do Iguaçu, and its relationship with space, socioeconomic variables and the built environment. The data were obtained from the Nutrition and Food Surveillance System, from 2009 to 2018. The demographic and socioeconomic data of the census sectors were obtained from IBGE (2010) and the information about the built environment form the Municipal Treasury Department. The nutritional status was classified as: marked thinness, thinness, eutrophic, risk of overweight, overweight and obesity. The methods applied were: georeferencing (Google Maps resources and QGIS program - version 3.4.8), temporal analysis (Minitab 18 and SPSS program), Moran's analysis (global and local) (GeoDA 1.12.1.131 program), and Spearman's correlation analysis (Minitab 18) to verify the relationship between the distribution of nutritional status proportion according to socioeconomic variables and the built environment. As a result, heterogeneity was evident among the South, Midwest, and North regions in the international border line municipalities of Brazil in the prevalence of different nutritional status of children aged 0 to 5 years, with higher percentages of marked thinness and thinness in the Midwest region and higher percentages of risk of overweight and overweight in the South region. The time series analysis indicated significant downward trend of extreme thinness and thinness in children aged 0 to 5 years in the borderline municipalities of the North and Midwest regions and significant upward trend of the risk of overweight in the North region. In Foz do Iguaçu-PR, a high percentage of children aged 0 to 5 years with overweight and obesity was observed. High proportions of thinness, risk of overweight, and overweight/obesity presented a differentiated spatial distribution in the12 municipality, significantly associated at the population aggregate level with socioeconomic variables such as income, skin color, and number of residents per residence. The correlation between nutritional status and the built environment was not found except for the positive correlation between the snack bar rate and thinness, and it was found that the census sectors with nutritional diagnoses present a predominance of census sectors by High-Low dissimilarity, indicating possible concentration of establishments in some regions of the municipality, making access tothese establishments difficult. We conclude that the findings indicate that a change in the nutritional profile of children aged 0 to 5 years in the Brazilian borderline municipalities is underway, with a reduction in the proportion of children with thinness and an increase in the risk of overweight. Furthermore, in Foz do Iguaçu, nutritional problems consist of heterogeneous phenomena in space and are related to socioeconomic variables, suggesting that social inequities are important determinants of nutritional problems.